Improvement of mechanical and water absorption properties of plant protein based bioplastics. (December 2017) - Gómez-Heincke, Diana; Martínez, Inmaculada; Stading, Mats; Gallegos, Críspulo; Partal, Pedro
Abstract: Bioplastics deriving from plant proteins are becoming an increasingly popular source of raw material for plastic products since they are not only biodegradable but renewable resources. However, these bioplastics require improved mechanical and water absorption properties to be suitable for many applications, such as packaging. For this reason, this study considers potato and rice proteins as a new source for the manufacture of bioplastics. The proteins were mixed with different glycerol concentrations followed by thermomoulding at temperatures from 60 to 180 °C. The resulting bioplastic is characterized in terms of thermo-mechanical properties, water absorption and molecular weight distribution. Compared to well-known wheat gluten, these bioplastics required higher temperatures for their thermomoulding. However, both of them were more structured materials and exhibited less water absorption (e.g. as low as 9 wt.%) than those obtained for wheat gluten blend. Potato protein-based bioplastics showed complex modulus values comparable to synthetic polymers such as Low Density Polyethylene (LDPE). Graphical abstract: Highlights: Rice and potato proteins based bioplastics manufactured by combining mixing and thermomoulding processes. Thermomoulding temperature is the key processing parameter to enhance material viscoelastic properties. Water absorption capacity of bioplastics is affected by process conditions and protein source.